2020
DOI: 10.2499/p15738coll2.133931
|View full text |Cite
|
Sign up to set email alerts
|

Food marketing margins during the COVID-19 pandemic: Evidence from vegetables in Ethiopia

Abstract: It is widely feared that the COVID-19 pandemic will lead to a significant worsening of the food security situation in low and middle-income countries. One reason for this is the disruption of food marketing systems and subsequent changes in farm and consumer prices. Based on primary data in Ethiopia collected just before the start and a few months into the pandemic, we assess changes in farm and consumer prices of four major vegetables and the contribution of different segments of the rural-urban value chain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
4
16
0
Order By: Relevance
“…(2021) (this issue) also shows that income declines cause increases in food insecurity and particularly reduction in more expensive but also more nutritious foods like fruits, vegetables, and animal‐sourced foods. This is consistent with findings from a recent survey in Ethiopia (Hirvonen et al., 2021), which found that reductions in household food consumption mainly reduced purchases of nutrient‐dense foods such as fruit, meat, eggs, and dairy. These adjustments limit declines in calorie intake but reduce dietary diversity and increase deficiencies of micronutrient consumption with potentially lasting adverse consequences for human health and development.…”
Section: Key Findings From the Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…(2021) (this issue) also shows that income declines cause increases in food insecurity and particularly reduction in more expensive but also more nutritious foods like fruits, vegetables, and animal‐sourced foods. This is consistent with findings from a recent survey in Ethiopia (Hirvonen et al., 2021), which found that reductions in household food consumption mainly reduced purchases of nutrient‐dense foods such as fruit, meat, eggs, and dairy. These adjustments limit declines in calorie intake but reduce dietary diversity and increase deficiencies of micronutrient consumption with potentially lasting adverse consequences for human health and development.…”
Section: Key Findings From the Studiessupporting
confidence: 92%
“…Hirvonen et al. (2021) (this issue) study domestic vegetable value chains in Ethiopia and find that the supply of vegetables in Ethiopia's urban markets was severely affected by disruptions in transport and in the supply of key farm inputs, as well as by trade restrictions. In telephone interviews conducted among traders, transporters, and processors, value chain agents indicated that their businesses were seriously affected by the COVID‐19 pandemic.…”
Section: Key Findings From the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Food security and human development are intricately linked (Conceição et al, 2011), which shows potential human development implications as the lasting effect on the pandemic in Africa. It is not surprising, therefore, to notice increased concerns for food security on the continent (Hirvonen et al, 2020) because of the disruption to the trade of staple foods (Laborde et al, 2020) due to the enforcement measures to combat COVID‐19.…”
Section: Introductionmentioning
confidence: 99%